Program Unggulan dalam Pengembangan Kurikulum di Madrasah Ibtidaiyah: Flagship Programs in Curriculum Development at Madrasah Ibtidaiyah - Hermawan, Ganjar; Nugraha, Mulyawan Safwandy; Nursobah, Asep (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2023)
This research examines the implementation and management of curriculum development through the flagship program at MIT Persis 24 Rancaekek Kabupaten Bandung Rancaekek Bandung. The main focus includes the relationship between curriculum and education and the philosophical foundation underlying the preparation of the flagship program. The curriculum is positioned as a strategic instrument in achieving educational goals. This research uses a qualitative approach with a field study method and the theoretical framework of education management and curriculum theory. The results showed that curriculum management which includes planning, organizing, implementing and evaluating plays an important role in the effectiveness of program implementation. A well-structured curriculum supports the integration of general and religious knowledge. Excellent programs such as Tahfidz, Tahsin, Nahwu Science, Sharaf, Mahfudlat, Ushul Fiqh, and Hadyu Rasul are designed to strengthen Islamic character and increase the competitiveness of educational institutions. The implementation of this program has a positive impact on the school's image and public interest in choosing MIT Persis 24 Rancaekek Kabupaten Bandung as a children's educational institution. Overall, the flagship program proved to be an effective strategy in improving the quality of education based on Islamic values.